Novel sigma (σ) receptor agonists produce antidepressant-like effects in mice - Wang, Jiajia (2007)
Many antidepressant drugs interact with σ receptors and accumulating evidence suggests that these proteins mediate antidepressant-like effects in animals and humans. σ Receptors are localized in brain regions affected in depression, further strengthening the hypothesis that they represent logical drug development targets. In this study, two novel σ receptor agonists (UMB23, UMB82) were evaluated for antidepressant-like activity in mice. First, radioligand binding studies confirmed that the novel compounds had preferential affinity for σ receptors. Second, the forced swim test, a well established animal model for screening potential antidepressant drugs, showed that both compounds dose-dependently reduced immobility time. The σ receptor antagonist BD1047 attenuated the antidepressant-like effects of UMB23 and UMB82. Third, locomotor activity suggested that the effects of UMB23 and UMB82 in the forced swim test were not due to non-specific motor activating effects. Together, the data provide further evidence that σ receptor agonists represent a possible new class of antidepressant medication.